Total Total Energy Intake, Ultra-Processed Food (UPF) Consumption and its Implication on the Nutritional Status of Adolescents of SMP PGRI Cibaribis, Bandung District : New Submit Iriyanti dkk - harun, iriyanti; Harun, Iriyani; Riana, Asysyifa; Irawan, Galuh Chandra (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Adolescent nutritional status reflects health conditions and is influenced by unbalanced diets, including high consumption of ultra-processed foods (UPF). This study aimed to analyze the relationship between total energy intake and frequency of UPF consumption with the nutritional status of adolescents at SMP PGRI Cibaribis, Bandung Regency. The research design used a quantitative observational analytic approach with a cross-sectional design. A sample of 71 students was selected using proportional random sampling technique. Data were collected through the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) and anthropometric measurements. Bivariate analysis using Chi-square test. Results showed the majority of respondents had high energy intake (36.6%) and frequently consumed UPF (76.1%). However, there was no significant relationship between energy intake and nutritional status (p=0.312) nor between frequency of UPF consumption and nutritional status (p=0.644). This finding indicates that both variables do not directly affect the nutritional status of adolescents. Future research is recommended to include other variables such as physical activity, consumption quality, and lifestyle factors that can affect nutritional status more comprehensively. Key words: energy intake, ultra-processed food (UPF), adolescents, nutritional status